Designing Augmented Reality Surah Al-Fatihah Application in Assisting Learning for Children - Abdul Meizar; Ambiyar; Unung Verawardina; Prasetyo (Jurnal Mantik, 2021)
The development of the world of technology which is getting more advanced every day has helped people to facilitate human activities such as military activities, government, offices, entertainment and others. One of them is education, with the application of sophisticated technology, of course, it can help activities in the teaching and learning system, one of which is the use of smartphones. Smartphones have now become a lifestyle and necessity among various people even among children who mostly depend on smartphones to fill their time every day, but this not only produces a positive side for the child but also gives negative impact on their life patterns. At this time many children use the smartphone only for games and entertainment, wasting a lot of time in vain and leaving the Qoran activities. This condition requires us to make smartphone use even more positive. So a learning application of the Al-Fatihah surah was designed using Android-based Augmented Reality which was designed and programmed using Unity 3D and Vuforia. In order to make children more interested in learning Surah Al-Fatihah.